2009
DOI: 10.1007/s10495-009-0328-8
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle arrest in early mitosis and induction of caspase-dependent apoptosis in U937 cells by diallyltetrasulfide (Al2S4)

Abstract: Naturally occurring organic sulfur compounds (OSCs), such as linear allylsulfides from Allium species, are attracting attention in cancer research, since several OSCs were shown to act beneficially both in chemoprevention and in chemotherapy, while hardly exerting any harmful side effects. Hence, we investigated the possible role of different OSCs in the treatment of leukemia. Thereby, we found that the compounds tested in this study induced apoptosis in U937 cells, with an efficiency depending on the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 76 publications
(121 reference statements)
4
39
0
Order By: Relevance
“…In line with the importance of sulfur, recent reports provided evidence that the biological activity of polysulfides directly correlates with their number of sulfur atoms, even if this relationship is not linear (Anwar et al, 2008). Thus, we found DATTS being the most active diallylsulfide in inducing apoptosis in U937 lymphoma cells, followed by DATS, whereas DAS and DADS instead were rather inactive (Cerella et al, 2009). Similarly, DATTS showed the highest antibiotic activity against Staphylococcus aureus (Tsao & Yin, 2001).…”
Section: Relevance Of Sulfur Atoms For the Reactivity Of Oscssupporting
confidence: 78%
See 2 more Smart Citations
“…In line with the importance of sulfur, recent reports provided evidence that the biological activity of polysulfides directly correlates with their number of sulfur atoms, even if this relationship is not linear (Anwar et al, 2008). Thus, we found DATTS being the most active diallylsulfide in inducing apoptosis in U937 lymphoma cells, followed by DATS, whereas DAS and DADS instead were rather inactive (Cerella et al, 2009). Similarly, DATTS showed the highest antibiotic activity against Staphylococcus aureus (Tsao & Yin, 2001).…”
Section: Relevance Of Sulfur Atoms For the Reactivity Of Oscssupporting
confidence: 78%
“…Some OSCs derived from Allium have been reported to possess an antioxidant activity (Borek, 2001). Due to their sulfur atoms, which can appear in up to ten different oxidation states (-2 to +6), these compounds can undergo redox-reactions (Cerella et al, 2009). Nishimura et al reported that Allium-derived organic sulfides and sulfoxides form in vivo sulfoxides and sulfones, respectively, by scavenging free hydroxyl (OH) or OOH radicals (Nishimura et al, 2000).…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Percentage of apoptotic cells was quantified as the fraction of apoptotic nuclei, as previously described assessed by fluorescence microscopy (Leica-DM IRB microscope, Lecuit, Luxemburg) upon staining with the DNA-specific dye Hoechst 33342 (Sigma) [37]. The fraction of cells with nuclear apoptotic morphology was counted (at least 300 cells in at least three independent fields).…”
Section: Analysis Of Apoptosismentioning
confidence: 99%
“…For instance, reactive oxygen species (ROS) generation seems to be one of the antiproliferative mechanisms of such compounds in cancer cells, but ROS levels seem to be closely dependent of the cell lines tested. For example, Cerella et al have reported that polysulfides induced a caspase-dependent apoptosis in U937 leukemia cells by activation of pro-apoptotic Bcl-2 family members and the release of the cytochrome c into the cytoplasm without ROS production (24). In contrast, Hosono et al showed that DAS 3 led to the formation of ROS in colon cancer cells, causing ß-tubulin oxidation and the disruption of the microtubule network, thus affecting the formation of --------------------------------------------------------------------------------------------------- -----------------------------------------------------------------------------------------------------a Effects of DAS 4 and DPS 4 (50 μM) on MCF-7 and Vcr-R cell cycle distribution after 24 h exposure.…”
Section: Discussionmentioning
confidence: 99%